2020
DOI: 10.29054/apmc/2020.858
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Suppurative Otitis Media Contributory Factors and their Prevention

Abstract: Background: Chronic suppurative otitis media has declined in the developed countries because of better health resources and better socioeconomic status of the people, but it still remains a major health problem in developing countries like Pakistan. Chronic suppurative otitis media (CSOM) is relatively common among illiterate people having poor socioeconomic status residing in the rural areas. Objective: To identify the contributory factors responsible for chronic suppurative otitis media and to devise strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Chronic suppurative otitis media (CSOM) is the most common disease in both paediatric and adult populations and is still a major health problem in developing countries. 1 Due to better usage of appropriate antibiotics, the incidence of intracranial and extracranial complications has declined. Meningitis is a common intracranial complication characterised by headache, fever, and neck stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic suppurative otitis media (CSOM) is the most common disease in both paediatric and adult populations and is still a major health problem in developing countries. 1 Due to better usage of appropriate antibiotics, the incidence of intracranial and extracranial complications has declined. Meningitis is a common intracranial complication characterised by headache, fever, and neck stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic suppurative otitis media (CSOM) is a persisting inflammation affecting the middle ear cleft for more than 3 months duration. 1 There are two types of CSOM, tubotympanic (mucosal), and atticoantral (squamosal) type. Atticoantral disease affects the attic, antrum, and mastoid.…”
Section: Introductionmentioning
confidence: 99%
“…The continued increase of middle ear pathologies in LMICs seems to be associated with multiple risk factors that are mainly predominant in these regions. In a study from Pakistan, Akhtar et al (2020) established factors contributing to the high prevalence of CSOM in their population. Their findings revealed that low socio-economic status, low educational level (below matric or Grade 12) and residence in rural areas were significant contributing factors to the high prevalence of CSOM in Pakistan.…”
Section: Risk Factors For Middle Ear Pathologiesmentioning
confidence: 99%
“…This, they asserted, is because of factors such as poverty, malnutrition, illiteracy, lack of health education, as well as people living in substandard and rural areas. Comprehensive preventive health care is, therefore, an urgent requirement (Akhtar et al 2020;Cordes et al 2018;, particularly where the burden of diseases that are risk factors for middle ear disease is reportedly high.…”
Section: Risk Factors For Middle Ear Pathologiesmentioning
confidence: 99%
“…This, they asserted, is because of factors such as poverty, malnutrition, illiteracy, lack of health education, as well as people living in substandard and rural areas. Comprehensive preventive health care is, therefore, an urgent requirement (Akhtar et al 2020;Cordes et al 2018;, particularly where the burden of diseases that are risk factors for middle ear disease is reportedly high.…”
Section: Risk Factors For Middle Ear Pathologiesmentioning
confidence: 99%